Bone-independent extramedullary disease is associated with inferior overall survival in multiple myeloma patients: a single center, real-world experience - Ke Xu; Charles Agbuduwe; Nickolaos Kanellias; William Wilson; Annabel McMillan; Xenofon Papanikolaou; Lydia Lee; Rakesh Popat; Jonathan Sive; Neil Rabin; Kwee Yong; Agapi Parcharidou; et al. (Haematologica)
Not available.